2020
DOI: 10.1149/1945-7111/ab82f7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Simultaneous Electrochemical Determination of Pb2+ and Cd2+ Based on Biomass Derived Lotus Root-Like Hierarchical Porous Carbon/Bismuth Composite

Abstract: A green and effective strategy to prepare a novel lotus root-like three-dimensional (3D) bismuth/biomass derived activated carbon (Bi@BAC) composite was developed for simultaneous electrochemical sensing of Pb 2+ and Cd 2+ . The BAC supports herein were prepared from naturally-abundant Platanus seeds chemically activation by KOH, with dense and uniform bismuth micro/nanosized particles successfully anchored on the carbon substrate through microwave-assisted hydrothermal treatment and subsequent carbothermal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…This electrocatalyst combined with a GCE (Pd@BAC/GCE) has been used for ultrasensitive and simultaneous determination of heavy metals Cd 2 + , Pb 2 + , and Cu 2 + . Zhu et al [88] have reported the incorporation of bismuth using Bi(NO 3 ) 3 .5H 2 O, through the solvothermal treatment at 150°C for 30 min under microwave irradiation, into BAC (Bi@BAC) derived by heating platanus seeds at 900°C for 2 h combined with KOH activation under N 2 flow.…”
Section: Electroanalysis Of Environmental Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This electrocatalyst combined with a GCE (Pd@BAC/GCE) has been used for ultrasensitive and simultaneous determination of heavy metals Cd 2 + , Pb 2 + , and Cu 2 + . Zhu et al [88] have reported the incorporation of bismuth using Bi(NO 3 ) 3 .5H 2 O, through the solvothermal treatment at 150°C for 30 min under microwave irradiation, into BAC (Bi@BAC) derived by heating platanus seeds at 900°C for 2 h combined with KOH activation under N 2 flow.…”
Section: Electroanalysis Of Environmental Pollutantsmentioning
confidence: 99%
“…Zhu et al [88] . have reported the incorporation of bismuth using Bi(NO 3 ) 3 .5H 2 O, through the solvothermal treatment at 150 °C for 30 min under microwave irradiation, into BAC (Bi@BAC) derived by heating platanus seeds at 900 °C for 2 h combined with KOH activation under N 2 flow.…”
Section: Electroanalysis Of Environmental Pollutantsmentioning
confidence: 99%
“…Heavy metals not only are unable to biodegrade but also tend to accumulate in body organs and tissues, which thereby represents a serious danger to human health according to the World Health Organization (WHO) 4,5 , even in trace levels. Lead (Pb) and cadmium (Cd) are examples of toxicant metals, originating from industrial emissions, that showed a worrying increase through the aquatic biosphere, and which have been recognized as potential hazards to human safety [6][7][8] . Lead is typically used in petroleum refining (over 50% of emissions) 5 , it is a potent neurotoxin and suspected carcinogen that can cause harm to the brain, red blood cells, lung disease, and kidney problems 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, loading and embedding nZVI particles on the surface of a template would extend their lifetime and effectively suppress their aggregation and oxidation. For this, biomass-derived porous carbon (BPC) is considered to be an ideal stabilizer and suitable material for dispersing nano iron particles due to its wide abundance and ecological role, as well as its structural, chemical, and thermal stability 8,24,[30][31][32][33] . Earlier research conducted by Chen et al, 34 and Song et al, 35 have shown that the carbon network could increase the reactivity of the iron particles through the Fe/C cross-link and thus increase the detection efficiency of heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biochar has been attracting immense interest for potential applications in the energy, adsorption and sensing fields due to its low cost, rapid regeneration, and green preparation methods [ 7 , 8 ]. On one hand, biochar typically has good electrical conductivity and a highly functionalized surface that contains peripheral groups that are able to chelate metal ions, providing a solid basis for HMIs sensing [ 9 ]. On the other hand, biochar is also regarded as an attractive adsorbent for HMIs owing to its large surface area, high degree of surface reactivity, and abundance of minerals.…”
Section: Introductionmentioning
confidence: 99%